From Bioactive Pyrrolidino[3,4-c]pyrrolidines to more Bioactive Pyrrolidino[3,4-b]pyrrolidines via Ring-Opening/Ring-Closing Promoted by Sodium Methoxide - Belveren, Samet; Larrañaga, Olatz; Poyraz, Samet; Dondas, H. Ali; Ülger, Mahmut; Şahin, Ertan; Ferrándiz-Saperas, Marcos; Sansano, José M.; de Gracia Retamosa, M.; de Cózar, Abel (Synthesis, 2019)
The process involving a rearrangement of pyrrolidino[3,4-c]pyrrolidine to another pyrrolidino[3,4-b]pyrrolidine using sodium methoxide as base is fully studied. The effects of the substituents are analyzed during the ring-opening/ring-closing sequence. Computational studies are also performed to explain the importance of susbstituents and quaternary carbons, especially when the (3-indolyl)methyl is present in the starting material. Finally, all the samples are evaluated as potential candidates for antibacterial and antimycobacterial activities.
Keywords: cycloaddition; azomethine ylides; rearrangement; antibacterials; DFT calculations